2009
DOI: 10.1007/s10649-009-9212-2
|View full text |Cite
|
Sign up to set email alerts
|

Working like real mathematicians: developing prospective teachers’ awareness of mathematical creativity through generating new concepts

Abstract: This paper describes the experience of a group of 17 prospective mathematics teachers who were engaged in a series of activities aimed at developing their awareness of creativity in mathematics. This experience was initiated on the basis of ideas proposed by the participants regarding ways creativity of school students might be developed. Over a period of 6 weeks, they were engaged in inventing geometrical concepts and in the examination of their properties. The prospective teachers' reflections upon the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 23 publications
0
29
0
5
Order By: Relevance
“…Considering the importance of creativity and using mistakes as potential avenues for learning mathematics (National Council of Teachers of Mathematics, 2000), negotiating relevant norms in classrooms is significant for prospective teachers. Many teachers are reported to not have the abilities needed for conducting activities that develop students' creativity, generally because of a lack of prior experience or proper teacher education (Shriki, 2005, as cited in Shriki, 2010). …”
Section: Conclusion and Implications For Mathematics Teaching And Tementioning
confidence: 99%
“…Considering the importance of creativity and using mistakes as potential avenues for learning mathematics (National Council of Teachers of Mathematics, 2000), negotiating relevant norms in classrooms is significant for prospective teachers. Many teachers are reported to not have the abilities needed for conducting activities that develop students' creativity, generally because of a lack of prior experience or proper teacher education (Shriki, 2005, as cited in Shriki, 2010). …”
Section: Conclusion and Implications For Mathematics Teaching And Tementioning
confidence: 99%
“…Scholars have presented various definitions, approaches, and interpretations regarding both mathematical and general creativity Shriki, 2010). Hadamard (1945) and Poincaré (1948) were inspired by the model of the creative process (Wallas, 1926) in their attempt to explain the creative thinking process of mathematicians.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shriki (2010) argued that teachers have insufficient knowledge regarding creativity. Bolden et al (2010) analyzed the written questionnaires and semi-structured interviews of prospective elementary school teachers regarding their conceptions of creativity, and revealed that these conceptions were narrow and related only to their own actions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Be to, matematikoje kūrybinio darbo rezultatas ne visada yra iš karto pritaikomas gyvenime (Shriki, 2010). Tačiau dažnai matematika kaip tik koncentruojasi į tai, kad būtų sukurti plačiai pritaikomi dalykai.…”
Section: įVadasunclassified